2019
DOI: 10.1200/jgo.18.00258
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Soft Tissue and Bone Sarcomas in Tanzania: Epidemiology and Clinical Features

Abstract: PURPOSE Pediatric sarcomas represent an important group of childhood tumors that require treatment at Muhimbili National Hospital (MNH), the largest pediatric oncology center in Tanzania. Treatment is often adapted from established childhood protocols validated in clinical trials from the United States and the United Kingdom. There are no studies describing the types of pediatric sarcomas most commonly seen in Tanzania to understand similarities and disparities with other countries and which sarcomas to priori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 14 publications
4
10
3
Order By: Relevance
“…8,21,25,27,28 In this study,the predominance of embryonal and alveolar RMS supports the literature on childhood occurrence of these subtypes of sarcomas while the very few cases of pleomorphic RMS in this study aligns with existing literature as well. 23,29 Other adult-type STS seen in this study differ somewhat in spectrum from those seen elsewhere. 27 Chondrosarcoma, epitheloid and clear cell sarcoma reported by Tinkle et al in the United states 27 were not seen in our study.…”
Section: 1contrasting
confidence: 41%
“…8,21,25,27,28 In this study,the predominance of embryonal and alveolar RMS supports the literature on childhood occurrence of these subtypes of sarcomas while the very few cases of pleomorphic RMS in this study aligns with existing literature as well. 23,29 Other adult-type STS seen in this study differ somewhat in spectrum from those seen elsewhere. 27 Chondrosarcoma, epitheloid and clear cell sarcoma reported by Tinkle et al in the United states 27 were not seen in our study.…”
Section: 1contrasting
confidence: 41%
“…This study found several sites to be affected predominantly in males similar to what has been found elsewhere where the orbit cervical lymph nodes and nasopharynx had male predominance. 2,12,15,23,[26][27][28][29] No sex predilection was found in terms of affection of the sinonasal region in this study but a study in Nigeria found male predominance but another from United States of America had female preponderance. Such differences may be accounted by variable epidemiological distribution of head and neck cancers.…”
Section: Discussionmentioning
confidence: 81%
“…Similar findings were reported in the study which was conducted by Khademi et al in Iran and Siwillis et al in Tanzania where the sinonasal cavity (nasal cavity plus paranasal sinuses) was predominantly affected by sarcomas. 27,30 This study had several limitations; the study was carried out in one tertiary hospital which may not be the representative of the entire country and the study being a snap shot experience over a relatively short period of time.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, the World Health Organization (WHO) report on classification of RMS includes four histological subtypes namely alveolar, embryonal, pleomorphic and sclerosing or spindle cell types of RMS [ 3 ]. It is estimated that embryonal RMS represents about 70% of all childhood RMS especially those below 10 years of age [ 4 , 5 ]. Of the head and neck regions, the orbit is the commonest site for embryonal RMS.…”
Section: Introductionmentioning
confidence: 99%
“…These results are due to multidisciplinary treatment approaches including surgery, radiotherapy and especially chemotherapy. RMS is a highly chemosensitive neoplasm, and the role of this therapeutic approach has also been clearly demonstrated in the adjuvant setting [ 5 , 10 ].…”
Section: Introductionmentioning
confidence: 99%